The meaning of Pangngadakkang in HRM practice: ethnographic study on creative SMEs in Toraja - Dipoatmodjo, Tenri Sayu Puspitaningsih (Journal Management & Economics Review (JUMPER), 2025)
This study explores the role of pangngadakkang—a Torajan cultural value centered on upliftment, respect, and mutual nurturance—in shaping human resource management (HRM) practices within creative micro, small, and medium enterprises (MSMEs) in Toraja, Indonesia. Using an ethnographic qualitative approach, data were collected over eight months through participant observation, semi-structured interviews, focus group discussions, and document analysis involving four creative MSMEs. The findings reveal pangngadakkang as an operative cultural grammar that redefines HRM across five themes: ethical leadership as moral custodianship, kinship-based recruitment and apprenticeship, ritualized workplace civility, moral economies of compensation, and youth-mediated technological modernization. These practices highlight a hybrid model of HRM that integrates modern business demands with deeply embedded cultural norms, fostering organizational resilience and worker dignity. However, tensions arise between cultural obligations and economic pressures, particularly in scaling enterprises and accessing formal finance. The study concludes that culturally informed HRM interventions, co-designed with communities and leveraging intergenerational knowledge exchanges, are essential to sustain Toraja’s creative industries. This research contributes to decolonizing HRM theory by foregrounding indigenous values as foundational to ethical and effective people management.